High‐rise plastic: Socio‐material entanglements in apartments. Issue 4 (21st June 2022) - Horne, Ralph; Dorignon, Louise; Middha, Bhavna
Abstract: Plastic is a persistent problem in westernised cities. Yet it is also a key mediator, affording and assisting the everyday. In small apartments, it supports daily life by assisting with waste management, storage, and provisioning of affordable ornaments and furniture. Plastic, in this context, is a mundane and utilitarian substrate to apartment life, as well as being a problematic potential pollutant. Recognising the diverse contributions to research on high‐density living, this paper draws on vertical urbanism and relational ideas of home. It explores the socio‐material entanglements of plastic in apartments through household interviews across Melbourne, London, Barcelona, and Perth. The research reveals ways in which plastic mediates the material inequalities of high‐rise living, typified by entanglements of space constraint, transience, and waste management. The contribution is twofold. Theoretically, our work suggests a direction for socio‐materialities research in reframing ideas of home as a static, physical site, to one that is more contingent materially and spatially. As various households adapt and make do, their refuges in the sky are being reconfigured physically and symbolically by and through plastic. Relational approaches can help to reveal the mundane but critical entanglements of plastic and everyday life in apartments. Second, empirically, we show that mundane infrastructures matter; they shape the spaces and places of plastic and apartment inequalities. Thus, policy interventions that target household behaviours can only have a marginal impact on plastic consumption where uneven infrastructures remain. Moreover, they may direct attention away from where change might be more promising, such as wider social rules and meanings around plastic, and the materialities of building design/management for waste infrastructures both inside and outside the apartment. Abstract : As a problem material, the elimination of plastic waste globally presents a particular challenge to ordinary and lower income apartment households that "make do" with the use of plastic. From a large empirical study, this paper analyses households' own accounts, revealing the socio‐material entanglements of plastic with waste, space, and time management. The authors point to the importance of spatial dimensions of domestic practices and the ways in which transience entangles with practice, influencing the meanings and logics of home.